CELIAC DISEASE IN ADULTS: RECENT ADVANCES IN EPIDEMIOLOGY, PATHOPHYSIOLOGY, DIAGNOSIS AND MANAGEMENT – CLINICAL CASE REPORT - Faiura, Oksana; Abrahamovych, Maryana; Tsyhanyk, Liliya; Guta, Solomiya; Drobinska, Nataliya; Ivanochko, Ruslana; Tolopko, Solomiya; Ferko, Mariia (Eastern Ukrainian Medical Journal, 2025)
Introduction. Celiac disease (CD) is a global public health problem. Recent studies have revealed the global prevalence of approximately 1.4% in adults. It is known to manifest usually in childhood and have different symptoms similar to other diseases. In the presented case reports the case of CD in adult, manifested by various atypical symptoms, that became the obstacle to diagnosis the CD in time was described. Methods. The review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We performed a comprehensive literature search using such databases as Web of Science, Embase, PubMed. The search strategy included the following terms: "celiac disease", "gluten sensitivity", "pathophysiology", "diagnosis and treatment", "case report". Case description was described according to Case Report (CARE) guidelines. Results. Recent advances in CD research have significantly enhanced our understanding of its epidemiology, pathophysiology, diagnosis, and management in adults. Advances in genetic and immunological research have deepened our understanding of disease mechanisms, paving the way for novel diagnostic and therapeutic approaches. А female patient had the complaints of constant pain in the periumbilical and left hypochondriac areas, irregular defecation, diarrhea; legs swelling up to the level of knees. During the ultrasonography of the internal organs, free fluid in the abdominal cavity (approximately 2.0l) was detected. During the gastroscopy it was found pyloritis, gastroptosis, gastroduodenal reflux, CD was suspected, biopsy was taken. The results of the duodenal descending part biopsy: chronic enteritis with significant atrophic-inflammatory changes. To confirm the CD the serological testing also was conducted: IgA to deamidated gliadin > 9.0 (N-<1.0), IgG to deamidated gliadin 0.22 (N-<1.0), IgA to tissue transglutaminase 2 – 2.88 (N-<1.0), IgG to tissue transglutaminase 2 – 0.06 (N<1.0). After the mentioned examination the diagnosis of CD was set. The patient received symptomatic treatment followed by the gluten-free diet (GFD). After 10 days in the hospital the patient was discharged with improved condition and the main recommendation to maintain the GFD. Discussion. CD is “getting older” and can be very similar to or accompanied by chronic pancreatitis, gastritis, irritable bowel syndrome etc. As could be seen from the clinical case description, the combination of the characteristic symptoms such as abdominal pain, bloating, continuous or frequently repeated diarrhea should lead to the thorough examination of a patient including endoscopy with biopsy and if any suspicion exists, subsequent serological testing. GFD remains the cornerstone of treatment, ongoing research into enzyme supplements, immunomodulators, and even genetic modification of wheat offers hope for additional management options. Conclusions. Only the multifaceted approach, combining serological tests, instrumental examinations and qualified histopathological assessment, offers a comprehensive means of identifying CD and enabling the timely treatment.